Evaluasi Sistem Informasi Akuntansi terhadap Pembayaran Klaim Nasabah pada Asuransi Perorangan di Asuransi Jiwa B - Rima Delly Desianawati; Rindang Widuri; Eka Novianti (Binus Business Review, 2013)
Life Insurance B is a company engaging in the services of people protection. Evaluation of accounting information system which relates with the customer claims payments made by the company has the objective to identify the weaknesses in the system of disbursement procedures and to provide the new recommendations. In doing the research, the author conducted literature research and field research. Fieldwork was conducted in order to obtain accurate and real data. Based on the research, writers found some weaknesses in the payment process customer claims, including the claim that the document is not to be numbered prints, the differences in the status of the policy and double claim status. There are weaknesses in the control applications such as sequence check, check and reasonable limits, total control check, which have not been applied to the company as well. In the company’s report, there has been no report on the problems that occur in a given period. To overcome these weaknesses, writers suggest a new document in the form of proposals that have been accompanied by a serial number printed. Should the company implement a weekly batch system with a view to have the latest report from branches every week, not every month. And finally the employees should make report any problems that occur in the company, so that problems that occur can be easily monitored by the authorities.